Peran Kepemimpinan Kepala Sekolah Berbasis Kearipan Lokal Sasak Dalam Peningkatan Kedisiplinan Kerja Guru - Muzakki Muzakki (Universitas Hamzanwadi, 2017)
The purpose of this study was to determine the leadership role of principals in improving the work discipline of NW NW Rumbuk teachers, so the authors present a theoretical study which presents theories related to the problem of this research. This study is located in MA NW Rumbuk Kec. Sakra, with research subjects namely principals, teachers and employees. Data collection techniques are carried out by observation, interviews, and documentation. By analyzing the data using Milles and Huberman model analysis. Based on the results of the study can provide an interpretation of the findings in the field, it can be said that, 1. Principals as managers have a strong role, coordinate, move and integrate all educational resources in schools. 2. Principals as educators of things that are taught by the principal are intelligence of the mind. 3. Principals as administrators, namely the principal must be able to carry out his duties properly. 4. Principals as motivators, principals are a very important part of school.